Increased PRR14 and VCAM-1 level in serum of patients with Parkinson's disease - Zheng, Huimin; Wang, Tai; Shi, Changhe; Fan, Liyuan; Su, Yun; Fan, Yu; Li, Xinwei; Yang, Jing; Mao, Chengyuan; Xu, Yuming (Frontiers in Neurology, 2022)
Background: Regarding the complexity of Parkinson's disease (PD), the identification of reliable biomarkers is of great significance for improving the accuracy of diagnosis and monitoring disease progression. Recently, some studies suggested that serum proline-rich protein 14 (PRR14), vascular cell adhesion molecule-1 (VCAM-1), and soluble CD163 (sCD163) factors may be associated with PD, even as potential biomarkers. However, the role of these serum factors is still unclear. Objectives: This study aimed to explore the alterations of serum PRR14, VCAM-1, and sCD163 levels during PD progression, and their association with disease-related variables of PD. Methods: We performed the assessment of scale tests and the detection of serum samples from PD patients (n=100) and healthy controls (HCs, n=100). Furthermore, we investigated the association between serum factors and sex, cognitive impairments, H&Y (Hohn and Yahr), age at onset (AAO), and other variables in PD patients. Results: PD patients exhibited increased PRR14 and VCAM-1 serum levels compared with HCs. No significant differences were found in serum levels of sCD163. Subgroup analysis uncovered increased VCAM-1 in the female and male subgroups (PD and HCs). Among patients with PD, decreased PRR14 and increased VCAM-1 were associated with severer cognitive impairments and severer PD (H&Y), respectively. Bivariate correlation analysis revealed that there was a positive correlation between VCAM-1 and AAO. Conclusions: Increased serum levels of PRR14 and VCAM-1 suggest that inflammation and defective autophagy may play vital roles in the pathogenesis of PD. However, the potential mechanisms remain to be elucidated.